2018
DOI: 10.1038/s41598-018-26506-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Administration of Conjugated Estrogen and Bazedoxifene Decreased Murine Fecal β-Glucuronidase Activity Without Impacting Overall Microbiome Community

Abstract: Conjugated estrogens (CE) and Bazedoxifene (BZA) combination is used to alleviate menopause-associated symptoms in women. CE+BZA undergo first-pass-metabolism in the liver and deconjugation by gut microbiome via β-glucuronidase (GUS) enzyme inside the distal gut. To date, the impact of long-term exposure to CE+BZA on the gut microbiome or GUS activity has not been examined. Our study using an ovariectomized mouse model showed that CE+BZA administration did not affect the overall cecal or fecal microbiome commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 52 publications
(53 reference statements)
2
41
0
Order By: Relevance
“…Albeit, the high ratio of circulating estrogen metabolites and parent estrogen aided by bGLU deglucuronidation activity in the gut is considered a risk factor for postmenopausal estrogen receptor positive (ERþ) breast cancer. Accordingly, a study on the therapeutic utility of this combination drug in an ovariectomized mouse model showed significant reduction in faecal bGLU activity without altering faecal microbiota diversity [208]. The study articulated the significance of bacterial bGLU inhibition to improving the outcome of long-term administered estrogens for postmenopausal women or breast cancer patients.…”
Section: Indole-based Hybridsmentioning
confidence: 99%
“…Albeit, the high ratio of circulating estrogen metabolites and parent estrogen aided by bGLU deglucuronidation activity in the gut is considered a risk factor for postmenopausal estrogen receptor positive (ERþ) breast cancer. Accordingly, a study on the therapeutic utility of this combination drug in an ovariectomized mouse model showed significant reduction in faecal bGLU activity without altering faecal microbiota diversity [208]. The study articulated the significance of bacterial bGLU inhibition to improving the outcome of long-term administered estrogens for postmenopausal women or breast cancer patients.…”
Section: Indole-based Hybridsmentioning
confidence: 99%
“…The sequence reads were processed in Mothur (v.1.42.3;Schloss et al, 2009) on the Niagara supercomputer at the SciNet HPC Consortium (Loken et al, 2010;Ponce et al, 2019). Operational taxonomic unit (OTU) picking was performed against SILVA ribosomal RNA database (132 release; Quast et al, 2013;Chen et al, 2018). Data interpretation, statistical analysis, and visualization were performed in MicrobiomeAnalyst (Dhariwal et al, 2017), including rarefaction to the minimum library size without scaling of data (Liu et al, 2017;Kaczmarek et al, 2019).…”
Section: Data Analysesmentioning
confidence: 99%
“…The growth of this species may have been influenced by interactions between endogenous estrogen and HE supplementation, as this reduction was not observed in OVX HE animals. This idea is supported by Chen et al, who observed a decrease in A. muciniphila in OVX mice supplemented with combined conjugated estrogens plus Bazedoxifene (a selective estrogen receptor modulator), along with a decrease in deconjugation enzymes [55]. Akkermansia muciniphila utilizes intestinal mucin as its sole energy source [56] and the degradation of mucins stimulates the regeneration of new mucin by epithelial cells, and releases mucin metabolites that are utilized by other bacteria in the lumen.…”
Section: Discussionmentioning
confidence: 86%